YIELD ANALYSIS OF CATFISH (CLARIAS SP.) NUGGET PROCESSING AT UMKM ADISYAFIDZ BAROKAH, BANDUNG - Panjaitan, Pola Sabar Tumohon; Ningsih, Trisna; Salmah, Zia Putri (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
Catfish (Clarias sp.) is a highly available aquaculture commodity widely used as raw material for value-added processed products, such as fish nuggets. Yield serves as a critical parameter in processing, directly influencing production efficiency, raw material utilization, and business profitability. This study aims to determine yield values at each stage of fish nugget processing from catfish at UMKM Adisyafidz Barokah, Bandung. Methods employed include direct observation, production practice, interviews, and weight recording of materials at every processing stage .Results indicate yields of 81.16% at the fish cleaning stage, 48.63% at filleting, 91.92% at dough mixing, and 145.72% for the final nugget product. The high final yield is attributed to the addition of ingredients like flour, seasonings, and breadcrumbs, which increase the product's final mass. Overall, these findings provide insights into production efficiency and serve as a basis for developing strategies to enhance value addition and optimize fish processing businesses in UMKM